CHANGES IN PARASYMPATHETIC CARDIOVASCULAR AUTONOMIC FUNCTIONS DURING THE MENSTRUAL CYCLE IN MEDICAL STUDENTS FROM BIDAR, KARNATAKA: A DESCRIPTIVE CROSS-SECTIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
The menstrual cycle is associated with cyclical fluctuations in estrogen and progesterone that influence cardiovascular autonomic regulation through modulation of parasympathetic activity. This study evaluated changes in parasympathetic cardiovascular autonomic function across different phases of the menstrual cycle in healthy young female medical students. A cross-sectional observational study was conducted among 105 healthy female medical students aged 18–21 years at Bidar Institute of Medical Sciences, Karnataka. Participants underwent autonomic function testing during the menstrual, follicular, and luteal phases of a single menstrual cycle. Parasympathetic cardiovascular function was assessed using resting heart rate (RHR), the 30:15 ratio, the Expiration:Inspiration (E:I) ratio, and the Standing:Lying (S:L) ratio. Data were analyzed using repeated-measures analysis of variance followed by Bonferroni post-hoc comparisons, with statistical significance set at p < 0.05. The 30:15 ratio and E:I ratio were significantly higher during the follicular phase than during the menstrual and luteal phases (p = 0.001 and p = 0.006, respectively), indicating enhanced parasympathetic activity. Resting heart rate differed significantly across menstrual phases (p = 0.009), whereas the Standing:Lying ratio showed no significant variation (p = 0.563). These findings demonstrate that parasympathetic cardiovascular autonomic function varies across the menstrual cycle, with greater vagal activity during the estrogen-dominant follicular phase. Consideration of menstrual phase may therefore improve the interpretation of cardiovascular autonomic function tests in healthy young women.